Islamic Education Curriculum Design Based on Inclusive Learning Management - Kurnialoh, Nasri; Farid, Akhmad; Musayaroh; Zakariyah; Maftuhah (AT-TAJDID: Journal of Islamic Education, 2025)
The curriculum is a planned and implemented program aimed at achieving specific goals. Therefore, learning management in education requires a concept that functions as a tool capable of adapting to the evolving times. This study analyzes the design of the Islamic Education curriculum, including its definition, components, and characteristics. The research method employed is library research. The findings reveal that the curriculum includes detailed management of learning, such as the types of educational materials, suggestions for teaching strategies, program development for effective implementation, and other activities aimed at achieving the desired objectives. In designing an Islamic Education curriculum based on learning management, several aspects must be considered, including alignment with the inclusive nature of humanity, accommodating the interests of the Muslim community, being realistic, comprehensive, and sustainable.